Cover Picture: Effect of Ganglioside GM3 Synthase Gene Knockout on the Glycoprotein N‐Glycan Profile of Mouse Embryonic Fibroblast (ChemBioChem 1/2013). Issue 1 (23rd December 2012) - Nagahori, Noriko; Yamashita, Tadashi; Amano, Maho; Nishimura, Shin‐Ichiro
<x xml:space="preserve">Abstract</x> The cover picture shows that gene knockout of the enzymes responsible for glycosphingolipid (GSL) synthesis significantly influences the biosynthesis of glycoprotein N‐glycans. On p. 73 ff., S.‐I. Nishimura et al. describe how they have established a general and comprehensive glycomics protocol of cellular GLSs and N‐glycans of glycoproteins. To test the feasibility of a glycoblotting‐based protocol, whole glycans released both from GLSs and glycoproteins were profiled concurrently by using the GM3 synthase‐deficient mouse embryonic fibroblast GM3(−/−). GM3(−/−) cells did not synthesize GM3 or any downstream product of GM3 synthase. Instead, expression levels of o‐series gangliosides involving GM1b and GD1‐α were increased dramatically whereas a‐/b‐series gangliosides were predominantly detected in wild‐type cells. It was also discovered that glycoprotein N‐glycan profiles of GM3(−/−) cells are significantly different from those of WT cells, though GM3 synthase is responsible only for GSL synthesis and is not associated with glycoprotein N‐glycan biosynthesis.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>